2020
DOI: 10.1074/jbc.ra120.014229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of a Na+-pumping NADH-ubiquinone oxidoreductase play multiple roles to block enzyme function

Abstract: The Na+-pumping NADH-ubiquinone (UQ) oxidoreductase (Na+-NQR) is present in the respiratory chain of many pathogenic bacteria and is thought to be a promising antibiotic target. While many details of Na+-NQR structure and function are known, the mechanisms of action of potent inhibitors is not well understood; elucidating the mechanisms would not only advance drug design strategies but might also provide insights on a terminal electron transfer from riboflavin to UQ. To this end, we performed photoaffinity lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
4
14
0
Order By: Relevance
“…This is probably because the binding site of UQ in NqrA, which may be located near the inhibitor binding site (18), is influenced by the mutation. While IC50 values of korormicin A and aurachin D-42 determined in the NADH-UQ1 oxidoreductase assay with the wild-type enzyme were one-digit nM levels (18,19), 50% inhibition was not observed for either inhibitor with the mutant, even at 2.0 µM.…”
Section: Structures Of Na + -Nqr With Bound Inhibitormentioning
confidence: 89%
See 1 more Smart Citation
“…This is probably because the binding site of UQ in NqrA, which may be located near the inhibitor binding site (18), is influenced by the mutation. While IC50 values of korormicin A and aurachin D-42 determined in the NADH-UQ1 oxidoreductase assay with the wild-type enzyme were one-digit nM levels (18,19), 50% inhibition was not observed for either inhibitor with the mutant, even at 2.0 µM.…”
Section: Structures Of Na + -Nqr With Bound Inhibitormentioning
confidence: 89%
“…Based on photoaffinity labeling experiments (18,19), we previously showed that korormicin A (a highly specific inhibitor of Na + -NQR, 18,20) and aurachin D-type inhibitors (naphthoquinone-like compounds) bind to a part of the protruding N-terminal stretch starting with transmembrane helix (TMH) 1 of NqrB (Try23−Lys54, Supplementary Figure 1) and that the UQ head-ring binds to the cytoplasmic region of NqrA close to the N-terminal stretch of NqrB (Leu32−Met39 and Phe131−Lys138, Supplementary Figure 1). Thus, the N-terminal stretch of NqrB (Met1−Lys54) may be critical for regulating the UQ reaction at the adjacent NqrA.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interface between NqrB and NqrA is itself of considerable interest. Masuya et al [ 44 ] used photoaffinity labeling studies to document inhibitor binding near a ubiquinone binding site [ 45 ] at this interface, proposing that the residues identified by Tuz et al [ 16 ] influence ubiquinone binding via indirect effects that lead to long-range structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…1,[13][14][15] Disruption of the chemiosmotic gradient generated by these redox complexes has the potential to arrest essential bacterial functions such as ATP synthesis, flagellar rotation, and nutrient transport. 11,16,17 Indeed, interruption of the Ftp gene in Listeria monocytogenes limited the bacterium's ability to grow on a carbon source that requires extracellular electron transport for utilization. 18 Thus, inhibitors of FMNylation (i.e., of Ftp) have the potential to curtail bacterial growth and therefore could lead to new antimicrobials to combat antibiotic-resistant bacteria, which are a growing menace.…”
Section: Introductionmentioning
confidence: 99%
“…It is now appreciated that Ftp's FMN‐transferase activity is required for the periplasmic FMNylation and electron‐transfer functions of subunits (e.g., NqrC and RnfG) of these flavin‐based cytoplasmic membrane‐bound NQR and/or RNF redox complexes, providing a link between those periplasmic functions and the redox reactions that occur within the bacterial cytoplasm 1,13–15 . Disruption of the chemiosmotic gradient generated by these redox complexes has the potential to arrest essential bacterial functions such as ATP synthesis, flagellar rotation, and nutrient transport 11,16,17 . Indeed, interruption of the Ftp gene in Listeria monocytogenes limited the bacterium's ability to grow on a carbon source that requires extracellular electron transport for utilization 18 .…”
Section: Introductionmentioning
confidence: 99%